2018
DOI: 10.1016/j.joi.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the quality of interactions and public engagement around scientific papers on Twitter

Abstract: This study explores science communication on Twitter by investigating a sample of tweets referring to academic papers in five different scientific fields. The specifications of science communicators on Twitter, the characteristics of those who initiate actions (by tweeting), the extent and quality of reactions (retweeting), individual and group interactions, and the distribution of tweets across types of engagement in the process of science communication (i.e., dissemination, consultation, and evaluation) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 16 publications
(12 reference statements)
5
39
1
1
Order By: Relevance
“…This provides evidence that Facebook is a platform that people outside academia use to publicly disseminate scientific publications to the public and professional networks. These findings support claims from previous studies that social web sites such as Facebook and Twitter can facilitate knowledge flows from academia to a broader audience (Didegah et al ., ; Mohammadi et al ., ; Na & Ye, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This provides evidence that Facebook is a platform that people outside academia use to publicly disseminate scientific publications to the public and professional networks. These findings support claims from previous studies that social web sites such as Facebook and Twitter can facilitate knowledge flows from academia to a broader audience (Didegah et al ., ; Mohammadi et al ., ; Na & Ye, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a content analysis of Twitter users who disseminated academic articles reported that the types of users differed across different disciplines. In particular, 62% and 43% were individual public accounts for Physical & Engineering and Social & Humanities journal articles, respectively, while 48% and 37% of users who tweeted Math & Computer and Social & Humanities, respectively, were scholars (Didegah et al ., ). A survey of users who tweeted scholarly information confirmed that just over half (55%) were in academia (Mohammadi et al ., ).…”
Section: Literature Reviewmentioning
confidence: 97%
See 2 more Smart Citations
“…In response to the increase in SNS popularity, individual scientists, research centers, and academic institutions are now frequently turning to Twitter to publicize scientific events and journal publications (Eysenbach, 2011;Peoples et al, 2016), and to communicate with their peers about science and research (López-Goñi and Sánchez-Angulo, 2017;Didegah et al, 2018). Twitter is also perceived by many scientists and research centers as a platform that can support science communication efforts with non-scientific audiences (López-Goñi and Sánchez-Angulo, 2017; Côté and Darling, 2018b;Didegah et al, 2018). As a result, scientists from diverse disciplines have analyzed Twitter to better understand how users interact and exchange information (Kwak et al, 2010;Stieglitz and Dang-Xuan, 2013;Didegah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%